تسخير الكنيسة للدين من أجل إشعال فتيل الحروب الصليبية - حسن, ياسين خضير (Al-Adab Journal, 2019)
The crusades are the most important aspects in the history of middle Ages, which represent significant field for the literature of both Muslims and western researches. They dealt with these topics by analyzing, searching and questioned events of their different aspects and campaigns. Traditional historians of crusades have characterized the crusades as religious wars which, according to their perspective, stemmed from the restoration of Jerusalem from the control of the Muslims under Seljuk.While most modern historians believe that the religious were one of the majorcauses that led to the outbreak of this war but it is not isolated from other political, economic and social matters of the European society, this chain of events combined to cause crusades. Increasingly, religious factor was only a tool used to convinced believers (Europeans Christians) that religious motivation of this war passion to be fuel of the later wars.